Analisis kinerja keuangan perusahaan sebelum dan semasa pandemi covid (2019-2020) pada perusahaan sektor farmasi yang terdaftar di BEI - Gwyneth Limbong (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2022)
Many businesses must maintain their financial performance in order to survive the COVID-19 pandemic. One of them is a pharmaceutical sector company that the public hopes can find a way to cure it. This study was conducted to determine differences in the financial performance of pharmaceutical sector companies listed on the IDX before and during the pandemic. The research data is secondary data taken from the Indonesia Stock Exchange website, namely 12 pharmaceutical companies. This type of research is quantitative research with a descriptive method approach. The financial performance is measured by the profitability ratios namelyreturn on assets, return on equity, net profit margin, gross profit margin and earnings per share. The result of this research is that only 2 out of 5 average profitability ratios, namely gross profit margin and earnings per share, have increased. The increase in market demand does not guarantee an increase in the company's financial performance, especially profit growth.